Global Police Index 2019 - Tinus Etsebeth (Zenodo, 2019)
Polisie | Polizei | 警察 | Police | شُرْطَة | ตำรวจ Freedom sets us apart. There are no bad police forces in the world, only unsupported forces. Unsupported by those they protect; the public, me and you. Governments see policing as a reactive organization, but being proactive is a necessity meaning availability of resources, equipment and technology. The lack of resources being the main contributor. The dissimilarity between police service and a police state in Africa, Europe, North America, South America, Asia. Developing police sciences and various specialities is an urgent need necessity, and the aim of improving the performance level of police affairs, meeting its requirements and strengthening the ability of its facilities, to discuss aspects of crime and delinquency in the legal context and without prejudice to the rights and freedoms of individuals. What is excluded in the index? Logically Thinking - Any military and private security personnel Data modules are excluded, only true police efficiency data. What is Authoritarian? Freedom of Movement - Authoritarianism is a form of government characterized by strong central power and limited freedom. Under an authoritarian regime, individual freedoms are subordinate to the state, and there is no constitutional accountability. I can't find my country? The simplest answer is there are 197 countries in the world, but in total there are 232 territories and regions that have some element of self-governance but are not considered sovereign states. 211 was taken into concentration, but only 177 had credible data to incorporate. Comprehensive data is only available for some countries, but don't worry; efforts are in place to list at least 98% of the world countries. Top Performing Forces Rank Score 1 Finland 0,056 2 Denmark 0,063 3 Switzerland 0,064 4 Austria 0,068 5 Iceland 0,073 5 Japan 0,073 6 Norway 0,089 7 Estonia 0,090 8 Luxembourg 0,091 9 United Kingdom 0,099 10 Australia 0,100 Under-Performing Forces Rank Score 126 Eritrea 0,347 127 Tajikistan 0,349 128 Yemen ...